Anthracene labeled poly(pyridine methacrylamide) as a polymer-based chemosensor for detection of pyrophosphate (P2O74−) in semi-aqueous media. Issue 47 (19th November 2020) - Roy, Saswati Ghosh; Mondal, Subhendu; Ghosh, Kumaresh
Abstract : Two polymers, linear P1 and cross-linked P2, are employed in anion sensing. P1 exhibits fluorescence sensing of HPPi with a detection limit of about 1.63 ppm in aqueous DMSO. P2 exhibits selective naked-eye detection of PPi/HPPi via an indicator displacement assay (IDA). Abstract : To develop fluorophore-labelled pyridinium-based macromolecular architectures for fluorometric and colorimetric detection of anions, two polymers P1 and P2 are synthesized. Linear polymer P1 and cross-linked polymer P2, prepared from N -methacryloyl-3-aminopyridine monomers via free radical polymerization followed by quaternization of the pyridine ring nitrogen with anthracene as a fluorescent marker, have been successfully employed in anion sensing. P1 exhibits excellent sensing of HPPi in aqueous DMSO. In addition to the enhancement of fluorescence emission of the anthracene moiety, P1 exclusively shows excimer/exciplex emission in the presence of HPPi over other anions and exhibits selectivity to HPPi with a detection limit of about 1.63 ppm. Cross-linked P2 exhibits naked-eye detection of PPi/HPPi over other anions studied via indicator displacement assay (IDA).